Judicial Reasoning in Banking Contract Defaults: A Case Study from Indonesian District Courts - Arifiyansyah, R. Muhammad Arfit; Sudirman, Lu; Situmeang, Ampuan; Fatihah, Nur (Journal of Judicial Review, 2025)
Banking customer default (wanprestasi) cases have increasingly dominated civil litigation in Indonesian district courts, particularly following the economic disruptions caused by the COVID-19 pandemic. While debtors frequently acknowledge contractual breach, courts are often confronted with non-juridical arguments based on economic hardship, creating a tension between strict contractual enforcement and the pursuit of substantive contractual justice. This study aims to analyze judicial reasoning in adjudicating banking customer default by examining Decision No. 22/Pdt.G.S/2023/PN Batam and assessing its conformity with the provisions of the Indonesian Civil Code. The research employs a normative juridical method using statutory and case approaches, relying on secondary legal materials including court decisions, statutory regulations, and legal doctrines. The findings reveal that the court consistently applied Articles 1239, 1243, and 1244 of the Civil Code, declaring the defendant in default due to failure to fulfill credit repayment obligations despite multiple formal warnings (somasi). Judicial reasoning was primarily grounded in written evidence and the debtor’s explicit acknowledgment of default, allowing the case to be resolved efficiently under the simplified lawsuit mechanism. The court ordered full repayment of the outstanding loan or, alternatively, authorized the auction of collateral through the State Assets and Auction Service Office (KPKNL). However, the analysis also indicates that the judgment predominantly emphasized legal certainty and contractual compliance while giving limited consideration to the debtor’s post-pandemic economic condition and request for installment relief. This study is significant as it demonstrates how simplified civil procedures reinforce creditor protection and procedural efficiency, yet simultaneously expose limitations in accommodating substantive contractual justice. The findings contribute to the development of default theory in banking law and provide critical insights for improving judicial responsiveness in contractual disputes involving socio-economic vulnerability.